Suicide seasonality and antidepressants: a register‐based study in Sweden. (8th June 2012) - Makris, G. D.; Reutfors, J.; Ösby, U.; Isacsson, G.; Frangakis, C.; Ekbom, A.; Papadopoulos, F. C.
<x xml:space="preserve">Abstract</x> Objective: Seasonality of completed suicides with a peak in spring and early summer is a well‐documented finding. The circannual serotonergic functioning is hypothesized to be central in this phenomenon. Antidepressant medications exert their pharmacological action mainly by regulating serotonin. Our aim is to study the amplitude of the seasonal effect among suicide victims positive for different classes of antidepressants or without any antidepressants at the time of death. Method: By using Swedish Registers, 12 448 suicides with forensic data for antidepressive medication and information on in‐patient‐treated mental disorder were identified during 1992–2003. Seasonality was estimated with a Poisson regression variant of the circular normal distribution of completed suicides. Results: Higher suicide seasonality was found for individuals treated with selective serotonin reuptake inhibitor (SSRIs) compared to those with other antidepressant treatment or without any antidepressant treatment. The finding is more evident for men and violent suicide methods and those without history of in‐patient treatment. Conclusion: Our results provide preliminary support for the serotonergic hypothesis of suicide seasonality and raise the question of a possible accentuation of the natural suicide seasonality in patients treated with SSRIs, a hypothesis that warrants further investigation.